Development of an endometriosis quality-of-life instrument: The Endometriosis Health Profile-30. - Jones, G; Kennedy, S; Barnard, A; Wong, J; Jenkinson, C (2001)
OBJECTIVE: To describe a new disease-specific questionnaire with established measurement properties that addresses the dimensions of health-related quality of life considered important to women with endometriosis. METHODS: The Endometriosis Health Profile-30 was developed in three stages. Stage 1 included open-ended exploratory interviews with 25 women to generate the items on the questionnaire. Stage 2 was an 87-item questionnaire administered in a postal survey to identify the most salient dimensions of health-related quality of life. In stage 3, the reliability and validity of the questionnaire were evaluated. RESULTS: The final instrument contained a core questionnaire with 30 items and five scales: pain, control and powerlessness, emotional well-being, social support, and self-image. Six modular parts consisting of 23 questions were also developed and measured the areas of sexual intercourse, work, relationship with children, feelings about the medical profession, treatment, and infertility. All the scales achieved high internal reliability, with Cronbach's alpha coefficient ranging from 0.83 to 0.93 (core questionnaire) and 0.79 to 0.96 (modules). The intraclass correlation coefficients to evaluate the test-retest reliability were high (range 0.88-0.98, P <.001). Content validity was demonstrated as the questionnaire was developed from interviews of patients rather than existing literature and clinical scales. Construct validity was assessed by correlating the Endometriosis Health Profile-30 scales with the relevant Short Form-36 scales. High correlations for all comparisons were found (-0.41 to -0.73). CONCLUSION: The Endometriosis Health Profile-30 is a reliable, valid, patient-generated instrument to measure the health-related quality of life of women with endometriosis. Its application in various health care settings will provide new and valuable information on the effect of endometriosis on health-related quality of life from the patients' perspective.